1987
DOI: 10.1063/1.453504
|View full text |Cite
|
Sign up to set email alerts
|

Observation and characterization of the CH5 radical by neutralized ion beam techniques

Abstract: Articles you may be interested inMass spectrometric detection of neutral radicals in a CH4 microwave discharge by use of Li+ ion attachment techniques Stability of the ammonium and methylammonium radicals from neutralized ionbeam spectroscopy The CHs (CDs) radical has been produced by charge transfer neutralization of fast ion beams using Na and Zn targets. The results obtained with Na targets are in excellent agreement with previous similar studies using alkali metal targets. In particular, no evidence for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nevertheless, it was also found that this movement was concerted to some extent. It is worth mentioning that the corresponding neutral system CH 5 • was observed and characterized by charge transfer neutralization of fast ion beams by using Na and Zn as targets (Selgren & Gellene, 1987). …”
Section: The Role Of Non‐classical Structures In Ion–molecule Intmentioning
confidence: 99%
“…Nevertheless, it was also found that this movement was concerted to some extent. It is worth mentioning that the corresponding neutral system CH 5 • was observed and characterized by charge transfer neutralization of fast ion beams by using Na and Zn as targets (Selgren & Gellene, 1987). …”
Section: The Role Of Non‐classical Structures In Ion–molecule Intmentioning
confidence: 99%
“…The transient CH 5 neutral has also been studied by neutralization reionization mass spectrometry, where CH 5 + was neutralized using an electron-donating species and the identity of the dissociation products were measured by mass spectrometry. The work presented here is similar in that CH 5 is formed by electron transfer from Cs, but the products are measured in coincidence, allowing for a complete kinematic description of the two-body dissociation along with branching fractions for each product channel.…”
Section: Introductionmentioning
confidence: 99%